2013
DOI: 10.1177/1538574413508828
|View full text |Cite
|
Sign up to set email alerts
|

Open Repair of Inflammatory Abdominal Aortic Aneurysm and Aortocaval Fistula Using Retrograde Balloon Occlusion

Abstract: Retrograde balloon occlusion of the inferior vena cava can be used to control hemorrhage during the open repair of an ACF, especially in the challenging setting of an inflammatory AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Unresolved issues in open repair, which was performed in our study, include the control of venous bleeding and the prevention of pulmonary embolisms caused by debris or air. In the present case, a balloon occlusion catheter was used to minimize intraoperative bleeding from the fistula, as previously reported [12,14] . Bleeding from the AVF can usually be controlled via digital compression.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Unresolved issues in open repair, which was performed in our study, include the control of venous bleeding and the prevention of pulmonary embolisms caused by debris or air. In the present case, a balloon occlusion catheter was used to minimize intraoperative bleeding from the fistula, as previously reported [12,14] . Bleeding from the AVF can usually be controlled via digital compression.…”
Section: Discussionmentioning
confidence: 86%
“…Consequently, the correct diagnosis is made in only 37–52% of cases before surgery [11] . Several case reports recommend the use of CT or duplex ultrasound as a means of diagnosing AVFs [12,13] . Any combination of imaging modalities, such as contrast-enhanced CT and abdominal ultrasonography, as used in this case, are useful, especially for regional diagnosis of AVF.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients undergoing an open repair had primary repair of the ACF from within the sac. Espinel et al 11 and Madani et al 46 used a retrograde balloon occlusion of the inferior vena cava (IVC) for venous control before primarily repairing the ACF. Four patients were repaired with a patch angioplasty of the IVC.…”
Section: Resultsmentioning
confidence: 99%
“…9,14 Occlusion of the IV or ICV with a balloon catheter inserted through the femoral vein has been used to prevent massive bleeding. 1,9,10 Espinel et al 1 suggested that this strategy should be routinely considered for open surgical repair of aortocaval fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…Catastrophic or lethal blood loss from inferior vein cava (IVC) or iliac vein (IV) can be controlled by digital or manual compression within the aneurismal sac, open vein clamping, or endovascular vein occlusion proximal and distal to the fistula. 1,6,9,10…”
Section: Introductionmentioning
confidence: 99%